Growth Response of Solanum melongena L. with Fly Ash-Bottom Ash Combination Planting Media and Compost Fertiliser - Jihan Ilfairah; Laila Hanum; Sarno Sarno (Newinera Publisher, 2026)
The increase in coal combustion waste such as fly ash and bottom ash (FABA) has encouraged its use as a soil conditioner to support sustainable agriculture. This study aims to determine the vegetative growth response of Solanum melongena L. to a combination of FABA and compost as a planting medium. The study was conducted from June to October [2025] at the Experimental Garden using a completely randomised design (CRD) consisting of six treatments and four replicates, namely T0 = soil (control), T1 = soil 100% compost, T2 = soil compost 75% + FABA 25%, T3 = soil compost 50% + FABA 50%, T4 = soil compost 25% + FABA 75%, and P5 = soil FABA 100%. The parameters observed included plant height, stem diameter, and number of leaves at 6-10 weeks after planting. The data were analyzed using ANOVA and followed by Duncan's test and BNT at a 5% level. The results showed that the combination of growing media had a significant effect on all vegetative growth parameters. The best treatments were T1 (100% compost) and T2 (75% compost-25% FABA) with plant heights of 15.9 cm and 11 cm, respectively, stem diameters of 5.8 mm, and 12.3 and 10.5 leaves, respectively. These findings demonstrate a practical, environmentally friendly method to improve crop growth and manage waste sustainably